Kesalahan Penulisan Gairaigo Pada Siswa SMA Pembangunan Laboratorium UNP - humaira, fhira; Yani, Damai (Universitas Negeri Padang, 2024)
Gairaigo is one of the lessons found in Japanese language learning. The difference in the form of writing gairaigo is divided into two types, first phonology in which there is complete absorption and the second morphology in which there is incomplete absorption makes Japanese language learning a lot of mistakes. This research focuses on the form and causes of gairaigo writing errors. The theory used in this research is the analysis of error forms from Kawarazaki (2004) and Tsujimura (2000) and the theory of the causes of errors from Pateda (in Qur'aini, 2018). The approach used in this research is descriptive qualitative. Data collection was conducted on students of UNP Laboratory Development High School class XII MIPA 3 using a research instrument in the form of a written test. There are two forms of gairaigo errors. First, phonological errors are full absorption gairaigo, the most errors are found in question number 5 at 58% occurring in the writing of consonant vocabulary [p] plus vowel [u] while the least error is found in question number 1 at 8% occurring in the writing of double consonants [-ed]. Second, morphological errors are incomplete absorption, the most errors are found in question number 19 by 72% occurring in the writing of single or basic laxem contractions while the least errors are found in question number 18 by 30% occurring in the writing of compositional or combined laxem contractions. And for the causes of errors found there are 4 namely, popular opinion, interference / mother tongue, environment and habits.